Thermodynamics of Bi2O3-SiO2 system - Onderka B.; Fitzner K.; Kopyto M.; Przybyło W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Thermodynamic properties of the liquid Bi2O3-SiO2 solutions were determined from the results of the electrochemical measurements by use of the solid oxide galvanic cells with YSZ (Yttria-Stabilized-Zirconia) electrolyte. Activities of Bi2O3 in the solutions were determined for 0.2, 0.3, 0.4, and 0.5 SiO2 mole fractions in the temperature range 1073-1293 K from measured electromotive force (e.m.f) of the solid electrolyte galvanic cell: Bi, Bi2O3-SiO2 | YSZ | air (pO2 = 0.213 bar) Additionally, heat capacity data obtained for two solid phases 6Bi2O3•SiO2 and 2Bi2O3•3SiO2 were included into optimization of thermodynamic properties of the system. Optimization procedure was supported by differential thermal analysis (DTA) data obtained in this work as well as those accepted from the literature. Using the data obtained in this work, and the information about phase equilibria found in the literature, binary system Bi2O3-SiO2 was assessed with the ThermoCalc software.